A numerical study on discrete combustion of polydisperse magnesium aero-suspensions. (1st March 2020) - Bozorg, Mehdi Vahabzadeh; Doranehgard, Mohammad Hossein; Hong, Kun; Xiong, Qingang; Li, Larry K.B.
Abstract: In this numerical study, discrete combustion of polydisperse magnesium dust clouds was investigated. A numerical model accounting for the effects of ignition, thermal conduction, and radiation was formulated to simulate the spatiotemporal distribution of temperature. Three distribution models, i.e., Dagum, log-normal, and Beta prime, were used to describe the magnesium particle-size polydispersity. The numerical model was first validated by comparison against experimental data on discrete combustion of both mono-sized and polydisperse magnesium aero-suspensions. Subsequently, the flame propagation characteristics of mono-sized and log-normally polydisperse cases at two different mean magnesium particle sizes were compared. The comparison shows that polydisperse magnesium dust clouds have higher flame propagation speeds than their mono-sized counterparts. Finally, the differences among the polydisperse cases with different size distributions were compared, revealing that magnesium powders with a higher percentage of small particles give rise to higher flame propagation speeds. Furthermore, results show that in comparison with the Dagum and Beta prime distributions, the log-normal distribution results in a lower flame propagation speed and a higher minimum ignition energy. As either the particle size decreases or the dust-cloud concentration increases, the flame propagation speed increases and the minimum ignition energy decreases. Highlights: Combustion of polydisperse magnesium dust clouds was numerically investigated. Numerical predictions agree well with experimental results. Three particle size distribution models were employed for particle polydispersity. Polydispersity leads to higher flame propagation and lower minimum ignition energy. The effects of particle size distribution models depend on mean particle size.